Cough expired volume and airflow rates during sequential induced cough - Hegland, Karen W.; Troche, Michelle S.; Davenport, Paul W. (Frontiers in Physiology, 2013)
Cough effectiveness is determined by a combination of volume of air expired and maximum expiratory airflow rate. Studies of cough sensitivity identify cough thresholds based on at least 2 or 5-cough re-accelerations to a stimulus, however to date no study has examined the interplay between the distribution of cough expired air and cough airflow rates for these induced sequential coughs. The goal of this study was to investigate the relationship between reflex cough re-accelerations, cough airflow and cough inspired and expired volume. Twenty adults (18–40 years, 4 men) volunteered for study participation, and were outfitted with a facemask in-line with a pneumotachograph and a one-way valve for capsaicin delivery on inspiration. Cough inspired and expired volume (Liters of air) as well as airflow parameters (peak expiratory flow rates L/s) were measured for each cough response. Results demonstrate significant linear relationships between cough expired volume, flow rates, and the total number of coughs produced. Thus, as the number of coughs in an epoch increase, the mechanical effectiveness of coughs within the epoch may decrease according to peak expiratory flow rates and cough expired volume, particularly for coughs comprised of more than 3 re-accelerations.